Changes in breeding phenology of eastern Ontario frogs over four decades. Issue 4 (26th February 2013) - Klaus, Samantha P.; Lougheed, Stephen C.
Abstract Global climate change has been implicated in phenological shifts for a variety of taxa. Amphibian species in particular are sensitive to changes in their environment due to their biphasic life history and restricted reproductive requirements. Previous research has shown that not all temperate amphibian species respond similarly to the same suite of climatic or environmental cues, nor are individual species necessarily uniform in their responses across their range. We examined both the timing of spring emergence and calling phenology of eight anuran species in southeastern Ontario, Canada, using an approximately 40‐year dataset of historical records of amphibian activity. Rana pipiens was the only species out of eight considered to emerge significantly earlier, by an estimated 22 days over four decades. Both R. pipiens and Bufo americanus have advanced initiation of calling over a four‐decade span significantly earlier by an estimated 37.2 and 19.2 days, respectively. Rana sylvatica showed a trend toward earlier emergence by 19 days, whereas we did not detect changes in emergence phenology for the remaining five species. This significant shift in breeding behavior for two species correlates to significant regional increases in spring temperatures of an estimated 2.7–2.8°C overall over four decades. Our study suggests that local temperature increases have affected the timing of emergence and the onset of calling activity in some Ontario anuran species. Global decline or range shifts ultimately may be related to changes in reproductive behavior and timing mediated by shifting climate.